Memberdayakan Manajemen Sumber Daya Manusia untuk Meningkatkan Kualitas Pendidikan SMA Negeri 2 Batang Anai - Lindra Lindra (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research combines qualitative methods and qualitative methods to the data collected by observation, interview, and literature research. The thing studied is the empowerment of high school students of SMAN 2 Batang Anai in implementing the School-Based Management Improvement Model, through the planning, implementation, monitoring and evaluation of empowerment activities. Empowerment is done is participative. The empowered are the teachers. The results showed that there is improvement of school quality in the field of Academic and Non-Academic field. The average school participant is 48% inactive category, 40%, and 11% inactive category. These results indicate an increase in the participation rate of school residents in the empowerment of human resources to improve the quality of schools. The result of task assessment from personnel of educational staff has increased in the last three years (2015, 2016, and 2017) with a good category, while for teacher's duty assessment in teaching has an average of 68.6% with the medium category.